Anti-proliferative and cytotoxic effect of Iranian snake (Vipera raddei kurdistanica) venom on human breast cancer cells via reactive oxygen species-mediated apoptosis - Ehsan Malekara; Mona Pazhouhi; Iraj Rashidi; Cyrus Jalili (Wolters Kluwer Medknow Publications, 2020)
Background and purpose: Breast cancer is the most commonly occurring cancer in women around the world. Despite new advances in cancer therapy, breast cancer remains a disease with high morbidity and mortality. Snake venom is a poisonous mixture of different molecules, such as carbohydrates, nucleosides, amino acids, lipids, proteins, and peptides. Previous studies demonstrated that some snake venoms showed in vitro anti-cancer effects. In this study, the effects of the Iranian snake (Vipera raddei kurdistanica) venom on breast cancer cells were investigated. Experimental approach: The effect of increasing concentrations of snake venom on breast cell viability was assessed by trypan blue, MTT, and lactate dehydrogenase measurements. Apoptosis was detected and quantified by fluorescent staining and DNA fragmentation assay. The expression level of some apoptotic-related genes was investigated using real-time polymerase chain reaction (RT-PCR). The Western blotting method was also used to detect the protein expression profiles in the cells. Findings / Results: After treatment for 24, 48, 72, and 96 h, the cell viability was significantly reduced in a time- and dose-dependent manner (P < 0.05). The venom effect on normal breast cells was significantly smaller than cancer cells (P > 0.05). Apoptosis was significantly increased (P < 0.05). The RT-PCR and western blot data confirmed the increase of apoptosis in cells treated with venom. Conclusion and implications: These data suggested that the vipera raddei kurdistanica venom had a cytotoxic property via activation of apoptosis in breast cancer cells.